A Pair-Electrosynthesis for Formate at Ultra-Low Voltage Via Coupling of CO2 Reduction and Formaldehyde Oxidation - Li, Mengyu; Wang, Tehua; Zhao, Weixing; Wang, Shuangyin; Zou, Yuqin (Nano-Micro Letters, 2022)
Formate can be synthesized electrochemically by CO2 reduction reaction (CO2RR) or formaldehyde oxidation reaction (FOR). The CO2RR approach suffers from kinetic-sluggish oxygen evolution reaction at the anode. To this end, an electrochemical system combining cathodic CO2RR with anodic FOR was developed, which enables the formate electrosynthesis at ultra-low voltage. Cathodic CO2RR employing the BiOCl electrode in H-cell exhibited formate Faradaic efficiency (FE) higher than 90% within a wide potential range from − 0.48 to − 1.32 VRHE. In flow cell, the current density of 100 mA cm−2 was achieved at − 0.67 VRHE. The anodic FOR using the Cu2O electrode displayed a low onset potential of − 0.13 VRHE and nearly 100% formate and H2 selectivity from 0.05 to 0.35 VRHE. The CO2RR and FOR were constructed in a flow cell through membrane electrode assembly for the electrosynthesis of formate, where the CO2RR//FOR delivered an enhanced current density of 100 mA cm−2 at 0.86 V. This work provides a promising pair-electrosynthesis of value-added chemicals with high FE and low energy consumption. Highlights: 1 Pair electrosynthesis of formate was achieved by combining CO2 reduction reaction (CO2RR) and formaldehyde oxidation reaction (FOR) in the membrane electrode assembly. 2 Replacing oxygen evolution reaction with thermodynamically more favorable FOR reduces energy consumption. 3 CO2RR//FOR exhibits excellent electrochemical performance (100 mA cm−2 @ 0.86 V), electricity consumption normalized by the mass of formate was 0.413 Wh g−1.